Free radical scavenging actions of virgin coconut oil - Jono Irawan; Aliefman Hakim; Saprizal Hadisaputra (Acta Chimica Asiana, 2022)
Natural antioxidants are quite popular in beauty products. In further product development, natural antioxidants are needed from local products of the NTB community. This study aims to optimize the antioxidant activity of local products Virgin Coconut Oil (VCO) from Cocos nucifera L. grown in Lombok. This type of research is experimental laboratory research using the DPPH method. VCO was isolated by conventional methods, namely standing and layered filtration. Data were obtained from the results of the UV-Vis spectroscopy test. The results showed that the free radical inhibition of VCO was strong, with an IC50 value of 51.57 and an inhibition of 48% at a 5% VCO concentration. The absorbance of DPPH decreased with increasing reaction time. The decrease in absorbance from every 5 minutes indicates the antioxidant activity continues to a stationary point. A color change indicates the stationary point to yellow. The strong antioxidant activity of VCO is used as the basis for its use as an active ingredient in various cosmetic products. VCO is also believed to have a function as a natural moisturizer.